Later Stuart Queens, 1660-1735: Religion, Political Culture, and Patronage. Edited by Eilish Gregory and Michael C. Questier. Cham: Palgrave Macmillan, 2023. ISBN 978-3-031-38813-2. xix + 368 pp - Alexander Ryland (Royal Studies Journal)
Later Stuart Queens,1660-1735: Religion, Political Culture, and Patronage. Edited by Eilish Gregory and Michael C. Questier. Cham: Palgrave Macmillan, 2023. ISBN 978-3-031-38813-2. xix + 368 pp